Representasi Nilai Dan Kepercayaan Konsumen Dalam Penjualan Manual Kuota Im3 Pada Era Digital - Aldi Bragy; Rina Pebriana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The digital era has brought with it various platforms for purchasing quotas quickly and easily, yet manual sales of IM3 quotas persists amidst these developments. This study aims to analyze the representation of consumer values ​​and trust in manual sales of IM3 quotas and to understand why consumers continue to choose manual channels in the digital era. This study uses a qualitative method with a descriptive approach, through interviews and observations of consumers and manual sellers of IM3 quotas. The results show that manual sales represent the values ​​of convenience, personal service, and transaction certainty that are perceived as important by consumers. Consumer trust is formed through direct interaction, repeated transaction experiences, and long-term relationships with sellers. These findings indicate that consumer perceptions of value and trust have not completely shifted to digital platforms. The results of this study align with consumer value theory and trust theory, which emphasize the functional, social, and emotional aspects of consumer decision-making. This study also confirms that manual sales retain strategic relevance by strengthening personal service, transaction transparency, and interpersonal relationships as an effort to maintain sales volume amidst the development of the digital era